8e Exposition Internationale de gravure. - Kosak, Miha; Krzisnik, Zoran; Biennale Ljubljana 1969 (Ljubljana : Moderna Galerija Ljubljana - Museum of Modern Art, 1969)
Abularach, Rodolfo ; Acero, Alfonso Quijano ; Ahlgren, Lauri ; Akritas, Al'bina ; Alexanco, José Luis ; Alim, Mariam M. Abdei ; Alsheikh, Yahia ; Alviani, Getulio ; Amano, Kunihiro ; Anaya, Fernando Lopez ; Anderle, Jiri ; Antes, Horst ; Apollonio, Marina ; Appel, Karel ; Araki, Tatsuo ; Armann, Gudmundur Sigurjönsson ; Baias-Lucaci, Ethel ; Bak, Imre ; Balcar, Jiri ; Ballif, Yannick ; Barbarigo, Ida ; Bates, Martin Pat ; Bednarova, Eva ; Behrakis, Georges ; Berber, Mersad ; Bergman, Anna-Eva ; Berni, Antonio ; Bernik, Janez ; Bertemes, Roger ; Bhatt, Jyoti ; Biasi, Alberto ; Bischof, Peter ; Bisti, Dmitrij ; Bitzan, Ion ; Böckman, Bengt ; Boljka, Janez ; de Bolle, Francis ; Bonomi, Maria ; Bontecou, Lee ; Borcic, Bogdan ; Braun, Theo ; Bresciano, Miguel ; Broniek, Zofia ; Bru, Roser ; Brunovsky, Albin ; Buchholz, Wolff ; Burghart, Toni ; Calhau, Fernando Pinto ; Capogrossi, Giuseppe ; Carcan, René ; Carmi, Eugenio ; Castro, Lourdes ; Celic, Stojan ; Charara, Mohssein ; Chehata, Farouk ; Childs, Bernard ; Chillida, Eduardo ; Corneille ; Cremer, Fritz ; Cumic, Mihailo ; Cvorovic, Slavoljub - Slavko ; Dabbagh, Salem ; Debenjak, Riko ; Deguide, Frédéric ; Dembo, Aleksander ; Denny, Robyn ; Diederen, Jef ; Djak, Zivko ; Dobrovic, Juraj ; Dorazio, Piero ; Dragulj, Emir ; Drawbridge, John ; Drebusch, Günter ; Droste, Karl Heinz ; Droungas, Achilles ; Dumouchel, Albert ; Edward, John ; Ekhard, Godwin ; Farrell, Michael ; Fiedler, François ; Flora, Anne ; Foissy, Georges ; Forsberg, Jan ; Fossier, Christian ; Franck, Paul ; Frankenthaler, Helen ; Friedlaender, Gotthard ; Frohner, Adolf ; Fukita, Fumiaki ; Fukuzawa, Shiro ; Gabrea, Serban ; Galic, Mladen ; Galvez, José Carlos Ramos ; Garache, Claude ; Gardy-Artigas ; Gasquet, Maurice ; Gébali, Hussein Al ; etc.
biografie
Frans
boek